Using Interactive Poster in Improving English Vocabulary of Vocational High School Students - Ovy Nawang; Sri Widodo; Andrian Nuriza Johan (Universitas Islam Negeri Palopo, 2026)
Vocabulary mastery is an essential component of learning English as a foreign language because it supports students’ ability to understand and communicate effectively. However, many vocational high school students still experience difficulties in mastering vocabulary due to limited learning media and low classroom engagement. Interactive posters present vocabulary through images, colors, keywords, and interactive activities that encourage students to participate actively during learning. In addition, the interactive posters integrated visual elements and task-based interactions to enhance students’ vocabulary engagement during the learning process. This study investigates the effectiveness of interactive poster media in improving students’ English vocabulary mastery. This study employed a quantitative method using a one-group pre-test and post-test design. The participants were 35 students of class XI BCF at a vocational high school in Purworejo. Data were collected through vocabulary tests administered before and after the treatment and analyzed using a Paired Sample T-Test. The findings showed that the mean score increased from 80.71 in the pre-test to 86.29 in the post-test, with a mean difference of 5.58 points. The statistical analysis revealed that the significance value (Sig. 2-tailed) was lower than 0.05, indicating a statistically significant improvement in students’ vocabulary mastery after the implementation of visual-interactive materials. Therefore, interactive posters can be considered an effective alternative learning medium to enhance students’ engagement and vocabulary learning outcomes.